Social Entrepreneurship dan Experiential Marketing Terhadap Corporate Image pada Warung Kopi Kiwari Bandung - Mohamad Hadi Prasetyo; Aep Saepudin (Forum Manajemen Indonesia (FMI), 2017)
The number of entrepreneurs in Indonesia is still quite low compared to countries in Asia. Efforts to increase the number of entrepreneurs should continue to bring economic progress to a country. In the process of development is also needed efforts to increase a sense of concern for social problems. The concept of entrepreneurship that combines business activities and social activities and has a goal to solve social problems known as the term Social Entrepreneurship. The object chosen in this research is Warung Kopi Kiwari. This store belongs to Social Entrepreneurship and engages in marketing strategies to enhance the experience. It was chosen because it saw a rapid growth in the coffee business. In a tight business competition, certainly every social entrepreneur needs to think about ways to keep his business running and the goal to solve social problems can be achieved. The purpose of this study is to determine the influence of Social Entrepreneurship and Experiential Marketing toward Corporate Image on Warung Kopi Kiwari Bandung. Data collection was done through questionnaires with a sample of 100 respondents and using path analysis. The results showed that Social Entrepreneurship and Experiential Marketing partially and simultaneously affect Corporate Image with standardized cofficient on Social Entrepreneurship variable of 30.1% and Experiential Marketing of 59.9% and probability value below 5%. Keyword: Social Entrepreneurship, Experiential Marketing, Corporate Image,and Kopi Kiwari Bandung